Facilitating Gender Audit : a guide for auditors, trainers and researchers - Government of Karnataka, Fiscal Policy Institute; UN Women (Bengaluru: Fiscal Policy Institute, 2019)
Since the adoption of Gender Budgeting as a tool in India in 2005-06, both national and state governments have provided support to various stakeholders in strengthening democratic governance and advancing women$1 (Bs rights through initiatives aimed at mainstreaming gender in policy planning and budgeting.The goal so far has been to equip government and non-government stakeholders with the requisite skills for implementing Gender Budgeting initiatives, and to prioritize resources. The next logical step is to understand how the allocations are spent through gender audits. In this direction, Fiscal Policy Institute initiated a project with the support from UN Women to prepare a hand book to facilitate auditors and trainers in gender auditing based on the actual field work. This hand book helps to promote conceptual and methodological understanding of engendering audits and arriving at Gender Audit Markers for conducting gender sensitive audits with a set of manuals, tools and practical guidelines to be used during the audit process..This handbook is intended as a working guide on how to conduct a gender audit of Government programmes, projects and schemes. It provides auditors and audit facilitators/trainers with an appropriate step-by-step approach on how to undertake a gender audit of programmes, projects and schemes. This is an outcome of several meetings, training programmes and pilot studies. Technical expert and technical advisory team and core team of FPI have substantially contributed to this hand book.s
Part A : Handbook & Tool kit -- Part B : Trainer's Manual The publication comprises of two parts. The first part is hand book for the trainees and the second part is a Trainers' Manual for the use of Resource Person. The handbook covers the key concepts of Gender, Gender Budgeting & Auditing, Linkage between Performance Indicator and Gender Market, Tool Kit on various schemes and programs along with Annexures of pilot gender audit report. The Trainers' Manual provides session plans with details of session topics, objectives, methodology of conducting training and suggestive resources. UN Women - Partner
Includes handout and bibliographical references
Keywords: Indira Mahendravada et al; Gender; Gender Budgeting and Auditing; Gender Market